Public Policy in Managing Palm Oil Industry Environmental Waste: A Qualitative Study in Kampar Regency, Indonesia - Veronika, Nina; Frinaldi, Aldri; Rembrandt, Rembrandt; Lanin, Dasman; Umar, Genius (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
Kampar Regency currently has the largest number of palm oil mills in Riau Province, which has led to an increase in environmental pollution due to the by-products of these industrial activities. The objective of this research is to identify the issues associated with waste management in palm oil mills. The research employs a descriptive-qualitative method to systematically, factually, and accurately represent the data contained in the news text. The results indicated that rubber and oil palm plantations (1.8 and 1.5 hectares) were inundated with waste. It is recommended that palm oil mills implement waste treatment in accordance with quality standards before disposal. Furthermore, the application of the law as the basis for sanctions from this waste must be accompanied by an appeal to the public to monitor the level of environmental pollution. In addition, the role of public policy actors in monitoring and determining legal sanctions for environmental pollution is of great importance.